One-Volt, Solution-Processed InZnO Thin-Film Transistors - Cai, Wensi; Li, Haiyun; Zang, Zhigang (IEEE electron device letters, 2021)
In this letter, we report solution-processed, high-performance Indium-Zinc-Oxide (IZO) thin-film transistors (TFTs). The annealing temperature of IZO films are studied and found that devices annealed at 350 °C exhibit the best performance. With the use of a thin Al x O y layer as the gate dielectric, one-volt IZO TFTs are demonstrated, showing a high current on/off ratio of > 10 5 , a high mobility over 10 cm 2 /Vs, and a low subthreshold swing (SS) of 83 mV/dec, which is fairly close to the theoretical limit of SS at 300 K. Such a high device performance is also found comparable to those deposited using vacuum-based methods. As a result, the presented devices might possess a great potential in low-cost, low-power electronics.